(untitled) (American Journal of Interdisciplinary Research and Development, 2026)
The article is dedicated to highlighting the theoretical significance of studying speech mastery in future officers. The article allows for a review of several issues related to the content and organization of teaching disciplines related to speech culture in military educational institutions.